Pengembangan Pocket Book Berbasis Pembelajaran Berdiferensiasi dalam Materi Pola Bilangan - Sumalinda, Lydia; Fadillah, Syarifah; Abdillah, Abdillah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Pocket books are a form of printed learning media that look almost the same as booklets, only they are designed to be smaller and more practical so they can be carried anywhere. The aim of this research is to produce development media in the form of a Pocket Book whose feasibility is seen. The method used in this research is research and development, with a research design according to Borg and Gall. This research was conducted at MTs Al Madani Pontianak with the research subjects being 26 students in class VIII B. The data collection tools used were validation sheets, teacher and student response questionnaires, and posttests. The data analysis techniques used in research include validity, practicality, and effectiveness. The data collection tools used were validation sheets, teacher and student response questionnaires, and posttests. Based on the results of data analysis, it was concluded that pocket books based on differentiated learning were suitable for use as learning media. With the pocket book validity level, the media validity criteria reached 85.64% with very valid criteria, and the material validity reached 86.06% with very valid criteria. The level of practicality of the pocket book is based on the results of the teacher response questionnaire and the results of the student response questionnaire. The results for the student response questionnaire were obtained with a percentage of 94.03%, the teacher response questionnaire with a percentage of 87% was in the very practical category. The level of effectiveness based on the hypothesis results can be concluded that the pocket book developed is effective